THE EFFECT OF DIFFERENT FEED TYPES ON THE ABSOLUTE WEIGHT GROWTH OF FRESHWATER LOBSTER SEEDS (Cherax quadricarinatus) 1 MONTH AGE - Hanafi Maulidditya Mukti; Sri Oetami Madyowati; Achmad Kusyairi; Nurul Hayati (Jurnal Perikanan Unram, 2024)
Fisheries cultivation in Indonesia includes ornamental fish cultivation and consumption fish cultivation. One of the problems in consumption fish cultivation is usually due to inappropriate feed factors, which makes the cultivation process tend to be long and inefficient. This research aims to determine the right type of feed to support the absolute weight growth of 1 month old freshwater lobster (Cherax quadricarinatus) seeds. The method used was an experimental method using a completely randomized design (CRD) with 5 treatments and 5 replications. The test animals used were 1 month old lobster seeds with an initial average weight of 1.60, the seeds were obtained from the spawning of the Krian lobster cultivation breeders. Lobsters were reared and given food according to treatment in the form of P1 (pellets), P2 (maggot), P3 (silk worms), P4 (potatoes, P5 (Daphnia magna) for 30 days. The results of the research showed that P3 silk worm food gave the highest absolute weight growth, namely 1.29gr, then maggot P2 which is 0.79gr, potato P4 0.64gr, then pellet P1 0.55g and finally daphnia magna with a figure of 0.17gr Absolute weight growth is the main parameter observed as well as supporting parameters including water quality including temperature , pH, and dissolved oxygen.